Chromatography column comparison and rapid pretreatment for the simultaneous analysis of amantadine, rimantadine, acyclovir, ribavirin, and moroxydine in chicken muscle by ultra high performance liquid chromatography and tandem mass spectrometry. Issue 20 (28th September 2016) - Zhang, Qiaoyan; Xiao, Chaogeng; Wang, Wei; Qian, Mingrong; Xu, Jie; Yang, Hua
Abstract : In this work, a chromatography column comparison and rapid pretreatment development were carried out. A multi‐class method was built based on the quick, easy, cheap, effective, rugged, and safe pretreatment method with hydrophilic interaction ultra high performance liquid chromatography and tandem mass spectrometry for the high‐throughput analysis of five antivirals in chicken muscle. The HSS T3 column, BEH HILIC column and BEH Amide column were studied, and their chemical functionalities and chromatographic separation effectiveness were compared. The BEH Amide column was selected to perform the mass spectrometry analysis under the hydrophilic interaction chromatography mode. First, a different strategy without adding MgSO4 and NaCl into the muscle samples was considered. Then, different concentrations of formic acid, acetic acid, and ammonia in acetonitrile were compared for better extraction efficiency. Nine sorbents (C18, PSA, NH2, Florisil, Alumina‐B, Alumina‐N, PestiCarb, NANO, and NANO‐NH2 ) were studied. The optimized procedure consisted of the use of 10% acetic acid in acetonitrile for the extraction solvent and NANO‐NH2 for clean‐up. NANO‐NH2 had not been applied in other matrix and pollutants so far. The developed method provided favorable trueness, precision, and acceptable matrix effect. Meanwhile, the method was sensitive, the limits of detection of amantadine, rimantadine, acyclovir, ribavirin, and moroxydine achieved were 0.56, 0.50, 0.30, 2.22, and 0.51 μg/kg, respectively, and were successfully applied for the routine detection of antivirals in the chicken samples.